HADITS TENTANG DARAH WANITA MENURUT AL-SHAN’ANI: Suatu Telaah Mukhtalaf al-Hadits - Zakiul Fuady Muhammad Daud; Irwanto Irwanto; Ahmad Khoirul Fata (Farabi, 2022)
Hadith is one of the sources of Islamic law, one of its functions is an explanation of the Qur'an. However, because hadiths are not always narrated mutawatir so there are some hadiths that seem contradictory (mukhtalif hadith). The purpose of this study was to determine the method of resolving mukhtalif hadiths about women's blood based on Imam as-Shan'ani's view contained in the book of Subul al-Salam. This research is a literature review that uses the book of Subul al-Salam as one of the primary data sources and uses content analysis as the method of analysis. The results showed that Imam Shan'ani resolve contradictory hadiths related to women's blood using the al-jam'u wa at-taufiq method or compromising the hadiths so that every muslim could practice mukhtalif hadiths customized according to their circumstances.